The Impact of Financial Depth Indicators on Economic Growth of Iraqi Banking Sector: An Analytical Study - et. al., Sundus Hameed Mousa Alktrani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to show the impact of indicators of financial depth on the economic growth of the Iraqi banking sector for the period (2005-2019), to help formulate economic policies aimed at "developing financial institutions and stimulating the process of economic growth, As well as identifying the economic and development effects of money presentation in GDP growth and measuring indicators of financial depth in the banking sector and its impact on economic growth, where the essence of financial center according to many financial theories lies in the call to give a central and rye role to the financial sector in influencing economic growth, where the results of the standard study resulted During the period (2005-2019) there was a positive impact between financial development and economic growth, by strengthening financial intermediation, developing reliable information systems on borrowers, improving access to credit and providing financial services to the poor in remote and rural areas. Diversifying banking services, reducing risk, reducing transaction and information costs to attract investors, which increases growth rates.